A long trip in the charming world of graphs for Pattern Recognition. Issue 2 (February 2015) - Vento, Mario
Abstract This paper is a historical overview of graph-based methodologies in Pattern Recognition in the last 40 years; history is interpreted with the aim of recognizing the rationale inspiring the papers published in these years, so as to roughly classify them. Despite the extent of scientific production in this field, it is possible to identify three historical periods, each having its own connotation common to most of the corresponding papers, which are called here as the pure, the impure and extreme periods.